A study on politeness strategies in the conversations of the course books “new cutting edge” by peter moor, sarah cunningham and jane comyns carr, published by longman in 2005 - Hoàng,Thị Thanh Huyền (ĐHĐN., 2015)
This thesis focuses on politeness strategies proposed by Brown and Levinson with references to both English and Vietnamese. This is a study focus on the aspect of semantics features of the conversations using politeness strategies in the course book ―new cutting edge‖. The findings are discussed and serve as a basis to put forward some implications for English teaching.